Síndrome de Burnout em Professores de Educação Física das Escolas Estaduais do Ensino Médio da Cidade de Pelotas/RS - Silva, Marta Solange Streicher Janelli da (2010)
This study is about a qualitative and quantitative study which shows the results obtained in the investigation which aimed to investigate Burnout syndrome, which is the relationship between working conditions and the falling ill of teachers due to poor working qualities. This research was devoted to 26 Physical Education teachers in public State schools in the city of Pelotas RS. The goal was verifying the working conditions through the testimony of the subjects involved in the research, and thus, enquiring work situations which contribute to the appearance of Burnout syndrome in these teachers. And also, this research tried to determine some features of the socio-demographic, occupational, and work-related personnel which may be associated to Burnout syndrome. The results obtained make reference to teachers-in-charge from secondary school, where the scope is mainly constituted by adults and teenagers from both the morning and the evening shifts. The instruments of investigation used were: Maslach Burnout Inventory (MBI), plus a semi-structured interview, which was applied to many teachers who presented features of Burnout. Obtained data have shown socio-demographic, occupational, working hours per week at school, gender, and professional formation. The results showed that three teachers presented high level of emotional exhaustion and depersonalization associated to low professional accomplishment, which characterize Burnout syndrome. By verifying the teachers‟ testimonies, other nuances were noted, not less important when it comes to working conditions as the importance of encouraging a debate about the role and working conditions of teachers of Physical Education, because the workload of teachers is a factor that interferes negatively on health and ultimately reflects in their family and social relationships.